Zones of normal convergence in the multi-dimensional case - Vilkauskas, L. (Lithuanian Mathematical Journal, 1961)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Л. Вилкаускас. Зоны нормальной сходимости в многомерном случаеL. Vilkauskas. Normalinio konvergavimo zonos daugiamačiu atveju